Fillers and Their Functions in Emma Watson’s Speech - Bernadeta Siska Indriyana; Maria Wisendy Sina; Barli Bram (Badan Pengembangan dan Pembinaan Bahasa, 2021)
Fillers are utterances or phrases that are used in speaking to fill in the moment of silence to connect thoughts or ideas. This paper investigated the types and functions of fillers used by Emma Watson in her speeches. The researchers formulated two questions to be resolved. First, what are the types of fillers used in Emma Watson’s speeches? Second, what are the functions of filler words in the speeches? Data, consisting of 93 occurrences of fillers, were collected from Emma Watson’s speech scripts in three videos. To solve the research questions, the researchers used the descriptive qualitative approach and discourse analysis. Results showed that Watson used two types of fillers, namely unlexicalized filled pauses (71 occurrences) and lexical filled pauses (22 occurrences) and five functions of fillers, namely hesitating, empathizing, mitigating, editing term and time-creating devices. AbstrakFiller atau kata pengisi merupakan ujaran atau frase yang digunakan dalam jeda percakapan untuk menghubungkan gagasan atau ide berikutnya. Makalah ini menyelidiki jenis dan fungsi kata pengisi yang digunakan oleh Emma Watson dalam pidatonya. Para peneliti merumuskan dua permasalahan. Pertama, apa jenis kata pengisi yang digunakan dalam pidato Emma Watson? Kedua, apa fungsi dari kata pengisi dalam pidato Emma Watson? Data, yang terdiri atas 93 kata pengisi, dikumpulkan dari tiga naskah video pidato Emma Watson. Untuk menjawab kedua permasalahan dalam studi ini, para peneliti menggunakan pendekatan kualitatif deskriptif dan analisis wacana. Hasil analisis menunjukkan bahwa Watson menggunakan dua jenis kata pengisi, yaitu jeda terisi non-leksikal (71 kali) dan jeda terisi leksikal (22 kali), serta lima fungsi kata pengisi, yaitu sebagai perangkat keragu-raguan, berempati, mengurangi efek, memperbaiki istilah, dan menambah waktu.